(3GdUGaj aj JaSjQ GdbQBfs - (3GdcGTj Ch GdcGTGfj, GdeJCdg GdMcje, eMSf Hf eQJVi Hf ajV Gddg eMehO, J (B1090 (3g`s
(3ChdgG (B:s
... (3dG MGLI dj EfeG YHGOJj ef MjK CQjO hbdfG jG BOe GScf CfJ hRhLc GdLfI (B.. (3hGdYdd hGdbeQ Yfg GdUGOb Ydi CfgG aj LfGJ GdOfjG JWdY ajg GdTeS hGdbeQ (B..s
(3BNQgG (B:s
.. (3haj QhGjI CNQi abGd hGdCFeI TjA ajchf CcHQ efg abjd (B.. (3haj GdJgPjH Yfg Cfg RGFQ efg bQGFI gPg GdBjI (B.. (3Je GdcJGH HYhf Gddgs
(3JHUQI GdeDda (B:s
(3jbhd GdRQcdj(B: (3hQO GSeg (B" (3eMSf Hf eQJVi (B" (3h (B" (3eMSf Hf eMqeO (B" (3h (B" (3eMeO eMSf (B" .s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 290s
(3GdPQjYI (B15\19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs